Helicobacter pylori CagA+ strains modulate colorectal pathology by regulating intestinal flora - Shasha Cui; Xinqiang Liu; Fengxia Han; Lu Zhang; Jingjing Bu; Sainan Wu; Jiafen Wang (BMC Gastroenterology)
Abstract Aim This article aims to investigate the role of Helicobacter Pylori (HP) CagA+ strains affected colorectal lesion via gut microbiota. Method 6-week C57BL/6J mice were divided into: (a) HP CagA+ group undergoing HP CagA+ strains administration by gavage at 0.2 mL for 10 days; (b) HP CagA- group undergoing HP CagA- strains administration by gavage at 0.2 mL for 10 days; (c) control group intragastrically given 0.2 mL of brian heart infusion (BHI) medium for 10 days. Gastric mucosa was collected for Giemsa staining, and colorectal mucosa was for hematoxylin and eosin (H&E) staining, 16 S ribosomal RNA (rRNA) sequencing and immunohistochemistry for Major Histocompatibility Complex (MHC). Colon tissues and serum from caudal vein was collected for quantification of interleukin (IL)-6, IL-8, IL10 and tumor necrosis factor (TNF-α). Results Mice with HP CagA+ infection developed loss of some resident cells and inflammation infiltration in colorectal mucosa, and increased Giemsa-positive cells in gastric tissue. Also, MHC II-positive cells were increased in colorectal tissue in HP CagA+ strains infection. HP CagA+ infection cause increase of TNF-α, IL-6, IL-8 and IL-10 in the serum. Meanwhile, HP CagA+ stainis evoked gut microbiota dysbiosis which was characterized by altered microbiome distribution, reduction in Front-to-Back (F/B ratio), decreased α-diversity metric (Chao1 and Shannon). In β-diversity, gut microbiota in control and HP CagA+ groups showed the significant distance based on UniFrac distance. Cag group was enriched a higher abundance of Staphylococcus and Corynebacterium, while control subjects were enriched in Marinifilaceae and Odoribacter. Conclusion HP CagA+ strains are capable of causing gut microbiota dysbiosis to develop destruction of intestinal barrier, and it may affect the development of colorectal cancer by increasing colonization of Staphylococcus and Corynebacterium.